2018
DOI: 10.5137/1019-5149.jtn.23808-18.3
|View full text |Cite
|
Sign up to set email alerts
|

New laminoplasty technique for preserving paravertebral muscles: technical note

Abstract: AIM: To develop a new laminoplasty technique for preserving paravertebral muscles. MATERIAL and METHODS: In this technique, semispinalis and splenius muscles are cut approximately 1 cm laterally to the muscle insertion point to the spinous process at the laminotomy side. Then, multifidus and rotatory muscles are dissected subperiosteally and retracted laterally. The posterior part of the spinous process is cut horizontally below the insertion point of the semispinalis and splenius muscles. At this point, all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Despite the development of various laminoplasty methods, such as a muscle preserving laminoplasty to resolve this problem, it is a more complex procedure than a conventional unilateral open-door laminoplasty at the C3 level. [12][13][14] Furthermore, high tension is applied to the tendinous portion in the intraoperative neck flexion position during surgery, which causes the C2 semispinalis cervicis to be highly vulnerable to thermal injury in the operative field. In a prior study by Lee et al, preservation of the C2 semispinalis cervicis was achieved in only 67% of patients after conventional laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the development of various laminoplasty methods, such as a muscle preserving laminoplasty to resolve this problem, it is a more complex procedure than a conventional unilateral open-door laminoplasty at the C3 level. [12][13][14] Furthermore, high tension is applied to the tendinous portion in the intraoperative neck flexion position during surgery, which causes the C2 semispinalis cervicis to be highly vulnerable to thermal injury in the operative field. In a prior study by Lee et al, preservation of the C2 semispinalis cervicis was achieved in only 67% of patients after conventional laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…17 Many muscle-sparing laminoplasty techniques have been developed based on this thesis for opendoor laminoplasty. 7,9,10,18 Many studies have focused on preserving the muscle attachment to the C2 or C7 spinous process, following demonstrations that muscle detachment at these levels greatly affect the incidence and severity of axial pain after laminoplasty. 19 The decompression of the C2 and C7 levels will be accompanied by the sacrifice of the cervical deep extensor, especially the semispinalis cervicis, which plays an important role in maintaining the lordosis and alignment of the cervical vertebrae.…”
Section: Essentiality Of Preserving Muscle Attachments In Laminoplastymentioning
confidence: 99%
“…23 And interestingly, reports of different posterior element-sparing techniques or restriction of the laminoplasty from C3 to C6 instead of C7 are shown to reduce kyphosis. 7,25,26 These studies have shown that when less of the posterior element is compromised, it may improve the lordosis of laminoplasty-treated patients and thus affect the overall clinical outcome. In our data, we found that HMP laminoplasty-treated patients showed slightly improved cervical lordosis even after 6 months of follow-ups, while the cervical lordosis was slightly reduced at the 6-months follow-up in the open-door laminoplasty group, with continued loss of lordosis at the 1-year follow-up (Table 3).…”
Section: Initial Outcome Of Hmp Laminoplastymentioning
confidence: 99%
See 1 more Smart Citation